Application of flat-joint contact model for uniaxial compression simulation of large stone porous asphalt Mixes. (30th March 2020) - Yuan, Gaoang; Li, Xiaojun; Hao, Peiwen; Li, Dewen; Pan, Junli; Li, Aiguo
Graphical abstract: Highlights: Flat-joint Contact Model was used for the first time to uniaxial compression simulation of asphalt mixture. The DEM model was realization using the real shape of aggregates. Mesoscopic parameters are determined based on virtual simulation results and laboratory test results. The relationship between microstructure parameters and macroscopic mechanical parameters is established. The energy distribution of uniaxial compression test was estimated by mechanic indication. Abstract: Discrete element method has been widely used to simulate performance indicators of asphalt mixture, but the contact model of particles is still the most key step in the simulation. The Flat-Joint Contact (FJC) model is a new theory to describe the contact conditions among the particles in granular materials, which is a new proposed model for geotechnical materials numerical simulation and has been integrated in the Particle Flow Code (PFC) recently. The applicability of the FJC model in Large Stone Porous asphalt Mixes (LSPM) is investigated in this paper. This paper rebuilds the irregular particles of field coring specimens using the image processing technology. Then, a three-dimensional discrete element program is developed to simulate the uniaxial compression test of LSPM with different aggregate gradations. The compressive strength, coordination number, contact point, and energy of LSPM are analyzed to characterize the performance in the testing process, and the simulation is compared with the laboratory testing to verify the reliability. Results show that the average coordination number can be used to evaluate the compressive strength, the four-parameter Boltzmann distribution can be used to describe the cumulative distribution probability of contact points. Energy indicator can be estimated by macroscopic compressive strength and reflected the mechanical property. Compared with the parallel bonding contact model (PBC), the FJC model simulation is closer to the laboratory test. Therefore, the proposed programs and FJC model are suitable to simulate the uniaxial compression process of the LSPM.